Aluminum oxide ceramic fiberboard with nano ceramic coating film and fireproof and heat-insulating functions

By covering the nanoceramic coating on the surface of the alumina ceramic fiberboard and combining specific adhesive components, the problem of insufficient fire and heat insulation in the construction field is solved, and higher corrosion resistance, adhesion and hydrophobic oleophobicity are achieved.

CN119735430AActive Publication Date: 2025-04-01CHANGZHOU TIANRUI NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510245364.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
2045-03-04

AI Technical Summary

Technical Problem

Existing ceramic fiberboards are difficult to meet the fire and heat insulation requirements in the construction field, and there are also shortcomings in adhesion, corrosion resistance, strength, bacteriostatic and hydrophobic oleophobicity.

Method used

Using nanoceramic coating technology, the fire insulation properties and adhesion are improved by covering the surface of the alumina ceramic fiberboard with hydroxylated layered Ti3C2/silica hollow spheres/ceramic particles, combined with chitosan/peony bark extract complex and acrylate emulsion.

Benefits of technology

It significantly improves the fire insulation properties, corrosion resistance, adhesion and hydrophilic oleophobic properties of alumina ceramic fiberboard, and meets the high standards requirements in the construction field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735430A_ABST
    Figure CN119735430A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, in particular to an aluminum oxide ceramic fiberboard with a nano-ceramic coating film and fireproof and heat-insulating functions, which sequentially comprises the nano-ceramic coating film and an aluminum oxide ceramic fiberboard from top to bottom, the nano ceramic coating film is prepared from the following raw materials in parts by mass: 50 to 70 parts of an adhesive, 10 to 20 parts of hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, 0.1 to 0.5 part of 2-acrylamido-2-sodium methylpropanesulfonate, 0.01 to 0.1 part of an initiator and 10 to 20 parts of water, the problem that in the prior art, a ceramic fiber board cannot meet the requirement for fire resistance and heat insulation of the ceramic fiber board in the building field is solved, and meanwhile the ceramic fiber board has excellent adhesive force, corrosion resistance, strength, antibacterial activity and hydrophobic and oleophobic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic technology, and more specifically to an alumina ceramic fiberboard with a nano-ceramic coating and fireproof and heat-insulating functions. Background Art

[0002] Ceramic fiber is a high temperature resistant fiber. Due to its light bulk density, high temperature resistance, good thermal stability and good chemical stability, it is widely used in the fields of automobile manufacturing, aerospace, furnaces, etc., and is also used in the field of construction. For example, the Chinese patent with the prior art publication number CN101081742A discloses a ceramic fiber building fireproof board. The technical solution is to use aluminum silicate fiber or light refractory filler as the base material, add one or more reinforcing fibers, and add an appropriate proportion of organic binder or inorganic binder, filler and additives, and make it through the processes of batching pulping, molding, drying and subsequent processing. The product obtained by this technical solution can effectively improve the fireproof grade, fire resistance limit, thermal insulation performance and strength of the building insulation board, and greatly reduce the volume density. However, the aluminum silicate fiber ceramic board is prone to cracking when it is impacted or bent. The Chinese patent with the authorization announcement number CN117069506B discloses a process for preparing a thermal insulation and noise reduction ceramic fiberboard; the thermal insulation and noise reduction ceramic fiberboard is made of the following raw materials in parts by weight: 50-60 parts of ceramic fiber material, 8-12 parts of the first functional agent, 10-14 parts of the second functional agent, 6-10 parts of filler, 15-25 parts of flocculant, 5-8 parts of binder and 25-35 parts of deionized water; the thermal insulation and noise reduction ceramic fiberboard preparation process provided by the technical solution, the prepared ceramic fiberboard can not only effectively reduce the thermal conductivity to improve the thermal insulation effect of the ceramic fiberboard, but also promote the effect of noise reduction; and it also has excellent flame retardant effect. However, the technical solution uses quartz fiber as the main component, and its thermal insulation performance at high temperature needs to be improved. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present invention aims to provide an alumina ceramic fiberboard with a nano-ceramic coating and fireproof and heat-insulating functions, so as to solve the problem that the ceramic fiberboard in the prior art cannot meet the fireproof and heat-insulating properties required by the construction field, and at the same time has excellent adhesion, corrosion resistance, strength, antibacterial properties, and hydrophobicity and oleophobicity.

[0004] To achieve the above-mentioned object, the present invention provides a nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions, which comprises a nano-ceramic coating and an alumina ceramic fiberboard from top to bottom; the raw materials of the nano-ceramic coating, calculated by mass, include: 50-70 parts of adhesive, 10-20 parts of hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, 0.1-0.5 parts of sodium 2-acrylamide-2-methylpropane sulfonate and 0.01-0.1 parts of initiator, and 10-20 parts of water; The preparation method of the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles comprises the following steps: respectively dispersing the hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles in water by ultrasonic method to obtain a hydroxylated layered Ti3C2 solution, a silicon oxide hollow sphere solution and a ceramic particle solution; mixing the hydroxylated layered Ti3C2 solution and the silicon oxide hollow sphere solution, stirring continuously for 6-10 hours at 40-70°C, adding the ceramic particle solution, stirring continuously for 3-6 hours, cooling, filtering and drying to obtain the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles.

[0005] Alumina ceramic fiberboard has a wide range of applications due to its good thermal insulation performance. However, when it is used in construction, pollutants such as sulfides and nitrides in the air react with water and oxygen to form acidic substances, and the pH of rainwater is either high or low, which causes the surface structure of the alumina fiberboard to be destroyed and reduce the thermal insulation performance. To solve the above problems, the inventors tried to coat the surface of the alumina fiberboard and found that when hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles were introduced, the alumina ceramic fiberboard had excellent corrosion resistance while further improving its thermal insulation performance. At the same time, the stability of the nano-ceramic coating was also improved. The inventors speculate that this is because the hollow silicon oxide spheres are attached to the surface of the hydroxylated layered Ti3C2 through hydrogen bonding, and the ceramic particles are filled between the lamellae of the hydroxylated layered Ti3C2, playing a supporting role, thereby avoiding the agglomeration and stacking between the lamellae and particles of the hydroxylated layered Ti3C2, so that the hydroxylated layered Ti3C2 / hollow silicon oxide spheres / ceramic particles can form a strong physical bond and bonding force on the alumina ceramic fiber board, thereby improving the adhesion of the nano-ceramic coating; at the same time, the hydroxylated layered Ti3C2 / hollow silicon oxide spheres / ceramic particles of this structure enable the nano-ceramic coating to effectively resist the erosion of corrosive media and by blocking the conduction of heat, the thermal insulation performance of the alumina ceramic fiber board is further improved through the nano-ceramic coating.

[0006] Preferably, the raw materials of the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles include hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles; the mass ratio of the hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles is (40-60): (2-5): (20-30).

[0007] Preferably, the hollow silicon oxide spheres are hollow silicon oxide spheres without a mesoporous structure.

[0008] Preferably, the ceramic particles include aluminum oxide with a particle size of 100-300 nm, silicon carbide with a particle size of 30-80 nm, and zirconium oxide with a particle size of 20-60 nm, and the mass ratio of the three is (10-15): (3-6): (2-4).

[0009] Preferably, the concentration of the hydroxylated layered Ti3C2 solution is 15-30 mg / mL; the concentration of the hollow silica sphere solution is 100-150 mg / mL; and the concentration of the ceramic particle solution is 100-150 mg / mL.

[0010] Preferably, the method for preparing the adhesive comprises the following steps: S1. Mix chitosan and water evenly to obtain a chitosan solution; mix the peony bark extract and water evenly to obtain a peony bark extract solution; mix the chitosan solution and the peony bark extract solution in a mass ratio of (2-3):1, and stir at 40-50°C for 30-50 minutes to obtain a chitosan / peony bark extract complex; S2, mixing water, sodium dodecylbenzene sulfonate and monomers, and adding ammonium persulfate to obtain an acrylate emulsion; the monomers include tridecafluorooctyl methacrylate, acrylate monomers and acrylic acid; S3. Evenly mix the chitosan / Paeonia suffruticosa Andrews extract complex and the acrylic emulsion to obtain the adhesive; the mass ratio of the chitosan / Paeonia suffruticosa Andrews complex to the acrylic emulsion is (5-8):1.

[0011] Alumina ceramic fiberboards used in construction also have the problem that molds are easy to breed in a humid environment, resulting in contamination or discoloration of the alumina ceramic fiberboards. In order to solve this problem, the inventors introduced chitosan / Paeonia suffruticosa extract complex and acrylic emulsion in the preparation process of the adhesive, and unexpectedly found that the chitosan / Paeonia suffruticosa extract complex not only exerts antibacterial properties, but also forms a protective film on the surface of the acrylic emulsion to reduce the adsorption and penetration of grease. Through the synergistic effect of the two, not only the breeding of molds on the surface of the alumina ceramic fiberboard is avoided, but also the nano-ceramic coating has a good hydrophobic and oleophobic effect, thereby avoiding the adhesion of water or grease on the surface of the alumina ceramic fiberboard.

[0012] However, since tridecafluorooctyl methacrylate is introduced into the present invention during the preparation process of the acrylic ester emulsion, the adhesion between the nano-ceramic coating and the alumina ceramic fiberboard is reduced. To solve the above problem, the inventors found that when sodium 2-acrylamide-2-methylpropane sulfonate is introduced, it can further make the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles evenly dispersed in the adhesive, and can react with the binder, especially with tridecafluorooctyl methacrylate, thereby avoiding excessive hardness of the nano-ceramic coating, thereby improving the adhesion between the nano-ceramic coating and the alumina ceramic fiberboard, and it can also further improve the hydrophobic and oleophobic effect of the nano-ceramic coating.

[0013] Preferably, the mass ratio of tridecafluorooctyl methacrylate, acrylate monomer and acrylic acid is (1-3): (8-12): (4-6).

[0014] Preferably, the mass ratio of water, sodium dodecylbenzene sulfonate, monomer and initiator is (40-60): (2-5): (20-30): (0.1-1).

[0015] Preferably, the acrylic acid ester monomer comprises methyl acrylate and ethyl acrylate in a mass ratio of (1-3):(1-3).

[0016] Preferably, the mass ratio of chitosan to water is 1:(20-30); the mass ratio of Paeonia suffruticosa Andrews extract to water is 1:(20-30).

[0017] Preferably, the initiator is selected from at least one of ammonium persulfate and potassium persulfate.

[0018] Preferably, the preparation method of the nano-ceramic coating comprises the following steps: uniformly mixing a binder and water, adding hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, sodium 2-acrylamide-2-methylpropane sulfonate and an initiator to obtain a mixture, sand-grinding the mixture to obtain a slurry, coating the slurry on an alumina ceramic fiber board, and heating and curing the slurry to obtain the nano-ceramic coating.

[0019] Preferably, the temperature of the heating curing is 40-60° C. and the time is 20-40 min.

[0020] Preferably, the thickness of the nano-ceramic film is 40-60 μm.

[0021] Preferably, the method for preparing the alumina ceramic fiber board comprises the following steps: Step 1, taking water and sodium silicate, mixing them evenly, adding phosphoric acid to adjust the system pH to 3, to obtain a sodium silicate solution; taking water and aluminum sulfate, mixing them evenly, to obtain an aluminum sulfate solution; taking water, ethanol, and zirconium oxychloride, mixing them evenly, adding hydrogen peroxide, and then adding ammonia water to adjust the system pH to 3, to obtain a zirconium oxychloride solution; mixing the sodium silicate solution, the zirconium oxychloride solution, and the aluminum sulfate solution, and stirring them at 60-80° C. for 4-6 hours; to obtain an inorganic binder; Step 2, mixing the alumina fibers and the inorganic binder, flocculating and breaking them up, and then dehydrating and forming to obtain a green body of the alumina ceramic fiberboard; Step 3: Drying and calcining the green body of the alumina ceramic fiber board to obtain the alumina ceramic fiber board.

[0022] Preferably, the alumina ceramic fiber board has a thickness of 5-8 mm.

[0023] Preferably, the mass ratio of water to sodium silicate is (1-1.2):1.

[0024] Preferably, the mass ratio of water to aluminum sulfate is (50-60):1.

[0025] Preferably, the mass ratio of water, ethanol, zirconium oxychloride and hydrogen peroxide is (1.5-2):(1.5-2):1:(1.2-1.5).

[0026] Preferably, the mass ratio of the sodium silicate solution, the zirconium oxychloride solution and the aluminum sulfate solution is 1:1:(2-4).

[0027] Preferably, the mass ratio of the alumina fiber to the inorganic binder is 1:(6-10).

[0028] Preferably, Al2O3 in the alumina fiber is ≥89%, the diameter of the alumina fiber is 9-12 μm, the bundle strength of the alumina fiber is 1.9-3.0 GPa, and the modulus of the alumina fiber is 300-360 GPa.

[0029] Preferably, the drying temperature is 90-110°C for 5-7h; and the calcination temperature is 1200-1500°C.

[0030] Alumina fiberboard has a maximum use temperature of 1600°C, has excellent fire resistance / fireproof performance, and has good thermal insulation performance, so it has a wide range of application prospects. However, the existing alumina fiberboard usually uses an organic binder or a combination of an organic binder and an inorganic binder in the production process, and the organic binder usually decomposes or burns at high temperatures, thereby causing the high-temperature fireproof performance of the alumina fiberboard to decrease. To solve this problem, the inventor has found through a large number of creative experiments that when the inorganic binder prepared by selecting sodium silicate solution, zirconium oxychloride solution and aluminum sulfate solution not only improves the strength of the alumina fiberboard, but also has excellent fireproof performance. The inventor speculates that on the one hand, the prepared inorganic binder has a small volume shrinkage rate after thermal decomposition, and can still maintain a high bonding strength at high temperatures. At the same time, the products of thermal decomposition, silicon dioxide, zirconium oxide and aluminum oxide, are also ceramic materials, which are dispersed in the alumina fibers, thereby further enhancing the strength of the alumina fiberboard and avoiding the decrease in the fireproof performance of the alumina fiberboard.

[0031] Preferably, the method for preparing the alumina ceramic fiberboard with the nano-ceramic coating and fireproof and heat-insulating functions comprises the following steps: preparing the alumina ceramic fiberboard and then preparing the nano-ceramic coating.

[0032] Beneficial Effects

[0033] 1. When the present invention introduces hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, the alumina ceramic fiber board has excellent corrosion resistance and further improves its thermal insulation performance, while also improving the stability of the nano-ceramic coating.

[0034] 2. The present invention introduces chitosan / Paeonia suffruticosa extract complex and acrylic emulsion in the preparation process of the adhesive, and unexpectedly finds that the chitosan / Paeonia suffruticosa extract complex not only exerts antibacterial properties, but also forms a protective film on the surface of the acrylic emulsion to reduce the adsorption and penetration of grease. Through the synergistic effect of the two, not only the reproduction of mold on the surface of the alumina ceramic fiberboard is avoided, but also the nano-ceramic coating has a good hydrophobic and oleophobic effect, thereby avoiding the attachment of water or grease to the surface of the alumina ceramic fiberboard.

[0035] 3. When sodium 2-acrylamide-2-methylpropane sulfonate is introduced into the present invention, it can further make the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles uniformly dispersed in the adhesive, and can react with the binder, especially with tridecafluorooctyl methacrylate, thereby avoiding the excessive hardness of the nano-ceramic coating, thereby improving the adhesion of the nano-ceramic coating to the alumina ceramic fiberboard, and it can also further improve the hydrophobic and oleophobic effect of the nano-ceramic coating.

[0036] 4. The inorganic binder prepared by the sodium silicate solution, zirconium oxychloride solution and aluminum sulfate solution selected in the present invention not only improves the strength of the alumina fiberboard, but also has excellent fireproof performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram of the structure of an alumina ceramic fiberboard with fireproof and heat-insulating functions having a nano-ceramic coating according to Example 1 of the present invention, wherein: 1 is the nano-ceramic coating, and 2 is the alumina ceramic fiberboard. DETAILED DESCRIPTION

[0038] In order to better explain the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the examples in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other implementation methods obtained by technicians in this field without creative work belong to the scope of protection of the present invention. The experimental methods in the following embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments and comparative examples can be obtained from commercial channels unless otherwise specified, including: The hydroxylated layered Ti3C2 was purchased from Nanjing Jicang Nanotechnology Co., Ltd. The hollow silicon oxide spheres without mesoporous structure were purchased from Beijing Beike New Materials Technology Co., Ltd. The aluminum oxide with a particle size of 200 nm was purchased from Guangzhou Hongwu Material Technology Co., Ltd. The silicon carbide with a particle size of 50 nm was purchased from Guangzhou Hongwu Material Technology Co., Ltd. The zirconium oxide with a particle size of 40±10 nm was purchased from Guangzhou Hongwu Material Technology Co., Ltd.; The chitosan was purchased from Shanghai Maokang Biotechnology Co., Ltd. The peony bark extract was purchased from Xi'an Zhanxun Biotechnology Co., Ltd. The sodium 2-acrylamido-2-methylpropane sulfonate was purchased from Guangzhou Yuejia Trading Co., Ltd. Nonylphenol polyoxyethylene ether was purchased from Guangzhou Yuejia Trading Co., Ltd., model: wetting emulsifier CO-630; Alumina fiber was purchased from Moron (Zhuhai) New Material Technology Co., Ltd., model: Moron 996; Tridecafluorooctyl methacrylate CAS: 2144-53-8; Acrylic acid CAS: 79-10-7; Methyl acrylate CAS: 96-33-3; Ethyl acrylate CAS: 140-88-5; Sodium dodecylbenzenesulfonate CAS: 25155-30-0; Ammonium persulfate CAS: 7727-54-0; Sodium silicate CAS: 1344-09-8; Aluminum sulfate CAS: 10043-01-3; Zirconium oxychloride CAS: 13520-92-8.

[0039] Example 1

[0040] A nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions, such as Figure 1 As shown, from top to bottom, it includes a nano ceramic coating 1 and an alumina ceramic fiber board 2; the raw materials of the nano ceramic coating 1 include, by mass, 60 parts of a binder, 15 parts of hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, 0.3 parts of sodium 2-acrylamido-2-methylpropane sulfonate, 0.05 parts of an initiator, and 15 parts of water; The preparation method of the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles comprises the following steps: respectively dispersing the hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles in water by ultrasonic method to obtain a hydroxylated layered Ti3C2 solution, a silicon oxide hollow sphere solution and a ceramic particle solution; mixing the hydroxylated layered Ti3C2 solution and the silicon oxide hollow sphere solution, stirring continuously for 8 hours at 50°C, adding the ceramic particle solution, stirring continuously for 5 hours, cooling, filtering and drying to obtain the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles.

[0041] The raw materials of the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles include hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles; the mass ratio of the hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles is 50:3:25.

[0042] The hollow silicon oxide spheres are hollow silicon oxide spheres without a mesoporous structure.

[0043] The ceramic particles include aluminum oxide with a particle size of 200 nm, silicon carbide with a particle size of 50 nm and zirconium oxide with a particle size of 40±10 nm, and the mass ratio of the three is 12:5:3.

[0044] The concentration of the hydroxylated layered Ti3C2 solution is 20 mg / mL; the concentration of the hollow silicon oxide sphere solution is 120 mg / mL; and the concentration of the ceramic particle solution is 120 mg / mL.

[0045] The preparation method of the adhesive comprises the following steps: S1. Mix chitosan and water evenly to obtain a chitosan solution; mix the peony bark extract and water evenly to obtain a peony bark extract solution; mix the chitosan solution and the peony bark extract solution in a mass ratio of 3:1, and stir at 45°C for 40 minutes to obtain a chitosan / peony bark extract complex; S2, mixing water, sodium dodecylbenzene sulfonate and monomers, and adding ammonium persulfate to obtain an acrylate emulsion; the monomers include tridecafluorooctyl methacrylate, acrylate monomers and acrylic acid; S3. Evenly mix the chitosan / Paeonia suffruticosa Andrews extract complex and the acrylic emulsion to obtain the adhesive; the mass ratio of the chitosan / Paeonia suffruticosa Andrews complex to the acrylic emulsion is 6:1.

[0046] The mass ratio of tridecafluorooctyl methacrylate, acrylate monomer and acrylic acid is 2:10:5.

[0047] The mass ratio of the water, sodium dodecylbenzene sulfonate, monomer and initiator is 50:4:25:0.3.

[0048] The acrylic acid ester monomers include methyl acrylate and ethyl acrylate, and the mass ratio of the two is 1:1.

[0049] The mass ratio of the chitosan to water is 1:25; the mass ratio of the peony bark extract to water is 1:25.

[0050] The initiator is ammonium persulfate.

[0051] The preparation method of the nano ceramic coating 1 comprises the following steps: uniformly mixing a binder and water, adding hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, sodium 2-acrylamide-2-methylpropane sulfonate and an initiator to obtain a mixture, sand-grinding the mixture to obtain a slurry, coating the slurry on an alumina ceramic fiber board 2, and heating and curing at 60°C for 30 minutes to obtain the nano ceramic coating 1.

[0052] The thickness of the nano-ceramic film 1 is 50 μm.

[0053] The method for preparing the alumina ceramic fiber board 2 comprises the following steps: Step 1, taking water and sodium silicate, mixing them evenly, adding phosphoric acid to adjust the pH of the system to 3, to obtain a sodium silicate solution; taking water and aluminum sulfate, mixing them evenly, to obtain an aluminum sulfate solution; taking water, ethanol, and zirconium oxychloride, mixing them evenly, adding hydrogen peroxide, and then adding ammonia water to adjust the pH of the system to 3, to obtain a zirconium oxychloride solution; mixing the sodium silicate solution, the zirconium oxychloride solution, and the aluminum sulfate solution, and stirring them at 70° C. for 5 hours; to obtain an inorganic binder; Step 2, mixing the alumina fibers and the inorganic binder, flocculating and breaking them up, and dehydrating and forming them to obtain a green body of the alumina ceramic fiber board 2; Step 3: Dry and calcine the green body of the alumina ceramic fiber board 2 to obtain the alumina ceramic fiber board 2.

[0054] The thickness of the alumina ceramic fiber board 2 is 6 mm.

[0055] The mass ratio of water to sodium silicate is 1.1:1.

[0056] The mass ratio of water to aluminum sulfate is 55:1.

[0057] The mass ratio of the water, ethanol, zirconium oxychloride and hydrogen peroxide is 1.8:1.8:1:1.4.

[0058] The mass ratio of the sodium silicate solution, the zirconium oxychloride solution and the aluminum sulfate solution is 1:1:3.

[0059] The mass ratio of the alumina fiber to the inorganic binder is 1:8.

[0060] The Al2O3 content of the alumina fiber is ≥89%, the diameter of the alumina fiber is 10.5±1.5 μm, the bundle strength of the alumina fiber is 2.7±0.3 GPa, and the modulus of the alumina fiber is 330±30 GPa.

[0061] The drying temperature is 100°C and the time is 6 hours; the calcination temperature is 1500°C.

[0062] The method for preparing the nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions comprises the following steps: preparing an alumina ceramic fiberboard 2 and then preparing a nano-ceramic coating 1.

[0063] Example 2

[0064] The difference from Example 1 is that the raw materials of the nano-ceramic coating include, by mass, 50 parts of adhesive, 10 parts of hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, 0.1 parts of sodium 2-acrylamide-2-methylpropane sulfonate, 0.01 parts of initiator, and 10 parts of water.

[0065] Example 3

[0066] The difference from Example 1 is that the raw materials of the nano-ceramic coating include, by mass, 70 parts of adhesive, 20 parts of hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, 0.4 parts of sodium 2-acrylamide-2-methylpropane sulfonate, 0.05 parts of initiator, and 20 parts of water.

[0067] Comparative Example 1 The difference from Example 1 is that the hydroxylated layered Ti3C2, hollow silicon oxide spheres and ceramic particles are directly mixed in a mass ratio of 50:3:25, and the rest are the same.

[0068] Comparative Example 2 The difference from Example 1 is that only acrylic emulsion is present in the adhesive, and the rest are the same.

[0069] Comparative Example 3 The difference from Example 1 is that only the chitosan / Paeonia suffruticosa Andrews extract complex is present in the adhesive, and the rest are the same.

[0070] Comparative Example 4 The difference from Example 1 is that sodium 2-acrylamido-2-methylpropane sulfonate is replaced by nonylphenol polyoxyethylene ether, and the rest is the same.

[0071] Comparative Example 5 The difference from Example 1 is that the sodium silicate solution is replaced by an aluminum sulfate solution of equal mass, and the rest are the same.

[0072] Comparative Example 6 The difference from Example 1 is that the zirconium oxychloride solution is replaced by an equal mass of sodium silicate solution, and the rest are the same.

[0073] Comparative Example 7 The difference from Example 1 is that the aluminum sulfate solution is replaced by an equal mass of sodium silicate solution, and the rest is the same.

[0074] Test Example: The alumina ceramic fiberboards with fireproof and heat-insulating functions and nano-ceramic coatings obtained in Examples 1-3 and Comparative Examples 1-7 were subjected to the following tests: 1. Adhesion: The adhesion of the nano-ceramic coating is evaluated according to the impact resistance in AAMA2605-05 7.5. If the nano-ceramic coating does not fall off, it is qualified, otherwise it is unqualified.

[0075] 2. Fire resistance: measured according to the specified method in JG / T564-2018 "Ceramic Fiber Fireproof Board for Building"; 3. Thermal insulation: ASTM-C201-1993 Standard test method for thermal conductivity of refractory materials to determine thermal conductivity; 4. Corrosion resistance: Measured according to the neutral salt spray test in GB / T 10125-2012; after 1000 hours of salt spray test, if there is no corrosion phenomenon in the nano-ceramic coating, it is qualified, otherwise it is unqualified; 5. Strength: Determine the compressive strength according to the provisions of GB / T 5072-2006 "Test method for compressive strength of refractory materials at room temperature"; 6. Antibacterial activity: Determined according to the method specified in JC / T 2039-2010; 7. Hydrophobicity and oleophobicity: Determined according to the method specified in GB / T 26490-2011 "Test Method for Super-amphiphobic Properties of Nanomaterials".

[0076] Table 1 Performance test results of the alumina ceramic fiberboards with fireproof and heat-insulating functions coated with nano-ceramic films of Examples 1-3 and Comparative Examples 1-7

[0077] It can be seen from Table 1 that the alumina ceramic fiberboards with fireproof and heat-insulating functions coated with nano-ceramic films of Examples 1-3 all have good adhesion, fireproofing, heat insulation, corrosion resistance, strength, antibacterial properties, and hydrophobicity and oleophobicity; In Comparative Example 1, since the hydroxylated layered Ti3C2, hollow silicon oxide spheres and ceramic particles were directly mixed at a mass ratio of 50:3:25, they did not form a composite, resulting in the obtained alumina ceramic fiber board having unqualified adhesion and corrosion resistance, and reduced thermal insulation, strength and hydrophobicity and oleophobicity; In Comparative Example 2, since there is no chitosan / Paeonia suffruticosa extract complex in the adhesive, the antibacterial property of the obtained alumina ceramic fiber board decreases, and the hydrophobicity and oleophobicity decrease to a greater extent; In Comparative Example 3, since there is no acrylic emulsion in the adhesive, the obtained alumina ceramic fiberboard is no longer hydrophobic and oleophobic; In Comparative Example 4, since sodium 2-acrylamide-2-methylpropane sulfonate was replaced with nonylphenol polyoxyethylene ether, the adhesion of the obtained alumina ceramic fiber board was unqualified, and the strength and hydrophobicity and oleophobicity were both reduced; In Comparative Example 5, the sodium silicate solution was replaced by an equal mass of aluminum sulfate solution; in Comparative Example 6, the zirconium oxychloride solution was replaced by an equal mass of sodium silicate solution; and in Comparative Example 7, the aluminum sulfate solution was replaced by an equal mass of sodium silicate solution, that is, the composition of the inorganic binder was changed, resulting in a decrease in the fire resistance level, thermal insulation and strength of the obtained alumina ceramic fiber board.

[0078] The above description is only a specific embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation made by the present invention, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

Claims

1. A nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions, characterized in that: From top to bottom, it includes a nano ceramic coating and an alumina ceramic fiberboard; the raw materials of the nano ceramic coating include, by weight: 50-70 parts of a binder, 10-20 parts of hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles, 0.1-0.5 parts of sodium 2-acrylamide-2-methylpropane sulfonate, 0.01-0.1 parts of an initiator, and 10-20 parts of water; The preparation method of the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles comprises the following steps: respectively dispersing the hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles in water by ultrasonic method to obtain a hydroxylated layered Ti3C2 solution, a silicon oxide hollow sphere solution and a ceramic particle solution; mixing the hydroxylated layered Ti3C2 solution and the silicon oxide hollow sphere solution, stirring continuously for 6-10 hours at 40-70°C, adding the ceramic particle solution, stirring continuously for 3-6 hours, cooling, filtering and drying to obtain the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles.

2. The nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions according to claim 1, characterized in that: The raw materials of the hydroxylated layered Ti3C2 / silicon oxide hollow spheres / ceramic particles include hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles; the mass ratio of the hydroxylated layered Ti3C2, silicon oxide hollow spheres and ceramic particles is (40-60): (2-5): (20-30).

3. The nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions according to claim 2, characterized in that: The hollow silicon oxide spheres are hollow silicon oxide spheres without a mesoporous structure.

4. The nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions according to claim 3, characterized in that: The ceramic particles include aluminum oxide with a particle size of 100-300 nm, silicon carbide with a particle size of 30-80 nm and zirconium oxide with a particle size of 20-60 nm, and the mass ratio of the three is (10-15): (3-6): (2-4).

5. The nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions according to claim 1, characterized in that: The preparation method of the adhesive comprises the following steps: S1. Mix chitosan and water evenly to obtain a chitosan solution; mix the peony bark extract and water evenly to obtain a peony bark extract solution; mix the chitosan solution and the peony bark extract solution in a mass ratio of (2-3):1, and stir at 40-50°C for 30-50 minutes to obtain a chitosan / peony bark extract complex; S2, mixing water, sodium dodecylbenzene sulfonate and monomers, and adding ammonium persulfate to obtain an acrylate emulsion; the monomers include tridecafluorooctyl methacrylate, acrylate monomers and acrylic acid; S3. Evenly mix the chitosan / Paeonia suffruticosa Andrews extract complex and the acrylic emulsion to obtain the adhesive; the mass ratio of the chitosan / Paeonia suffruticosa Andrews complex to the acrylic emulsion is (5-8):

1.

6. The alumina ceramic fiberboard with nano-ceramic coating and fireproof and heat-insulating functions according to claim 5, characterized in that: The mass ratio of tridecafluorooctyl methacrylate, acrylate monomer and acrylic acid is (1-3): (8-12): (4-6).

7. The alumina ceramic fiberboard with nano-ceramic coating and fireproof and heat-insulating functions according to claim 6, characterized in that: The acrylic acid ester monomer includes methyl acrylate and ethyl acrylate, and the mass ratio of the two is (1-3): (1-3).

8. The nano-ceramic coated alumina ceramic fiberboard with fireproof and heat-insulating functions according to claim 1, characterized in that: The method for preparing the alumina ceramic fiberboard comprises the following steps: Step 1, taking water and sodium silicate, mixing them evenly, adding phosphoric acid to adjust the system pH to 3, to obtain a sodium silicate solution; taking water and aluminum sulfate, mixing them evenly, to obtain an aluminum sulfate solution; taking water, ethanol, and zirconium oxychloride, mixing them evenly, adding hydrogen peroxide, and then adding ammonia water to adjust the system pH to 3, to obtain a zirconium oxychloride solution; mixing the sodium silicate solution, the zirconium oxychloride solution, and the aluminum sulfate solution, and stirring them at 60-80° C. for 4-6 hours; to obtain an inorganic binder; Step 2, mixing the alumina fibers and the inorganic binder, flocculating and breaking them up, and then dehydrating and forming to obtain a green body of the alumina ceramic fiberboard; Step 3: Drying and calcining the green body of the alumina ceramic fiber board to obtain the alumina ceramic fiber board.

9. The alumina ceramic fiberboard with fireproof and heat-insulating functions coated with nano-ceramic film according to claim 8, characterized in that: The mass ratio of the sodium silicate solution, the zirconium oxychloride solution and the aluminum sulfate solution is 1:1:(2-4).

10. The alumina ceramic fiberboard with fireproof and heat-insulating functions coated with nano-ceramic film according to claim 9, characterized in that: The Al2O3 content of the alumina fiber is ≥89%, the diameter of the alumina fiber is 9-12 μm, the bundle strength of the alumina fiber is 1.9-3.0 GPa, and the modulus of the alumina fiber is 300-360 GPa.

Citation Information

Patent Citations

  • Organic / inorganic composite gel plugging agent with rigid interior and flexible exterior, and preparation method thereof

    CN111218261A

  • High-temperature-resistant ceramic fiber board and preparation method thereof

    CN118754653A

  • Ceramic material for multilayer ceramic substrate and preparation method thereof

    CN118978390A

  • Aerogel paint with fireproof and heat insulation properties and preparation method thereof

    US20240343922A1